The purloining of Prince Oleomargarine - Twain, Mark, 1835-1910; Stead, Philip Christian (Yearling, 2021)
Based on rough notes from a story Mark Twain told his children one night in 1879. A lonely boy named Johnny is given magical seeds that allow him to speak to animals. This newfound gift propels Johnny into a quest to save a stolen prince.